1993
DOI: 10.1172/jci116160
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of T cells invading the skin during acute graft-vs.-host disease after semiallogeneic bone marrow transplantation.

Abstract: The mechanisms responsible for skin lesions during acute graft-vs.-host disease (aGVHD) after allogeneic bone marrow transplantation (BMT) are poorly understood. The exact role of various effector cell populations and "major" (particularly HLA-DP) or "minor" antigens as target molecules is not known. To investigate the nature of cells responsible for tissue injury, we cultured T cells from skin biopsy first with interleukin 2 (IL-2) alone and then in polyclonal activation conditions to avoid in vitro antigenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 33 publications
(11 reference statements)
1
20
0
Order By: Relevance
“…1), these results strongly suggested that each set of clones belonging to the same TCRBV family derived in fact from a single or a few T cell clones. These findings are also in agreement with our previous reports showing that T cells infiltrating the skin at the onset of GVHD were oligoclonal, and for a majority of them, host specific (11,12). Consequently, one clone representative of each subset was kept for further characterization.…”
Section: Origin and Specificity Of Clones Derived From Bil T Lymphocysupporting
confidence: 93%
See 3 more Smart Citations
“…1), these results strongly suggested that each set of clones belonging to the same TCRBV family derived in fact from a single or a few T cell clones. These findings are also in agreement with our previous reports showing that T cells infiltrating the skin at the onset of GVHD were oligoclonal, and for a majority of them, host specific (11,12). Consequently, one clone representative of each subset was kept for further characterization.…”
Section: Origin and Specificity Of Clones Derived From Bil T Lymphocysupporting
confidence: 93%
“…We have recently documented the presence of HLA-DP-specific T cells in the skin lesions of patients who developed GVHD after semiallogeneic BMT (11,12). In these previous examples, other HLA class I and class II incompatibilities were present in addition to the HLA-DP mismatch.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, we have demonstrated the presence of HLA-DP-specific T cells in the skin of patients who developed GVHD after semi-allogeneic BMT, each time an HLA-DP mismatch was present. [6][7][8] However, only once did we have the opportunity to analyze a graft setting where HLA-DP was the only documented mismatch in the GVHD direction. In that case, we could demonstrate that a large fraction of skin-infiltrating T lymphocytes expressing diverse T cell receptors were reactive against HLA-DPB1*0501, the only mismatch of the graft.…”
mentioning
confidence: 99%